2014
DOI: 10.3109/09638288.2014.882416
|View full text |Cite
|
Sign up to set email alerts
|

Navigating stroke care: the experiences of younger stroke survivors

Abstract: Stroke care can be conceptualised as a temporal field of social activity and relationships which shapes variations in experiences of care among younger stroke survivors, and differences in expectations of support at different time points after stroke. On entering the field of stroke participants reported needing health care professional guidance and expertise to manage the acute event, yet difficulties accessing information in hospital limited the agency of some individuals wanting to take an active role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…This can explain why older survivor age predicted higher caregiver QOL in our study. In fact, younger stroke survivors have more problems in term of identity, life satisfaction, social and sexual relationship, finances and support when they return to work (Martinsen, Kirkevold, & Sveen, ; Roding, Glader, Malm, & Lindstrom, ; Sadler, Daniel, Wolfe, & McKevitt, ). The association between higher survivor physical functioning and higher caregiver QOL was expected since better survivor physical functioning, as also reported in other studies (Ogunlana et al., ; Pucciarelli et al., ), represents fewer problems in caregiver life.…”
Section: Discussionmentioning
confidence: 99%
“…This can explain why older survivor age predicted higher caregiver QOL in our study. In fact, younger stroke survivors have more problems in term of identity, life satisfaction, social and sexual relationship, finances and support when they return to work (Martinsen, Kirkevold, & Sveen, ; Roding, Glader, Malm, & Lindstrom, ; Sadler, Daniel, Wolfe, & McKevitt, ). The association between higher survivor physical functioning and higher caregiver QOL was expected since better survivor physical functioning, as also reported in other studies (Ogunlana et al., ; Pucciarelli et al., ), represents fewer problems in caregiver life.…”
Section: Discussionmentioning
confidence: 99%
“…Nine research teams specifically addressed social support (Dumas et al., ; Dyson et al., ; Henderson et al., ; McKeever & Miller, ; Mithen et al., ; Noiesen et al., ; Sadler et al., ; Savage et al., ; Warin et al., ). When patients become disabled and ill, they often require personal medical services or other forms of social support that compensate for the effects of loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers used Bourdieu's theory to uncover that living with disabilities or illnesses is contingent on embodied dispositions shared by members of a social class. For example, Henderson et al (2014) and Sadler, Daniel, Wolfe, and McKevitt (2014) found that limited access to social support had a negative impact on disease management because social support networks often provided resources or capital needed to negotiate self-management activities. In contrast, access to social capital, such as family support, encouraged patients to follow health care professionals' guidelines (Dumas, Robitaille, & Jette, 2014;Mithen, Aitken, Ziersch, & Kavanagh, 2015;Noiesen, Larsen, & Agner, 2004;Savage, Dumas, & Stuart, 2013;Warin et al, 2008).…”
Section: Social Supportmentioning
confidence: 99%
See 2 more Smart Citations